Saudi Novel: Commencements, Efforts, and Headway - Yahya Saleh Hasan Dahami (Bulletin of Social Studies and Community Development, 2023)
Abstract: Thematic and artistic growth has seen significant modifications in the Saudi novel. Readers may be better able to comprehend the many developments that come after understanding the various stages of the Saudi novel's progress. Examining the origins, progression, and significance of the Saudi novel, a significant literary genre, has been done at every stage. The researcher uses an analytical-critical approach in this literary work in line with the goal of the literary analysis. After discussing a brief analysis of the Saudi novel as a literary work and an outline of the Saudi novel, the research opens with an overview of the contribution of Saudi women to the Saudi novel. The article's next portion offers a continuing analysis of the author Gimashah Al-Elian's sketching of the novel, The Female Spider. The study ends with a conclusion and helpful discussions.    Keywords: arabic novel, arabic literature, gimashah al elian, kingdom of saudi arabia, saudi fiction, saudi novel, the female spider.